Penerapan Metode Dikte å¬å†™ (TÄ«ngxiÄ›) dalam Peningkatan Kosakata Bahasa Mandarin - Muliani, Muliani; Saud, Syukur; Junaeny, Arini (Universitas Negeri Makassar, 2021)
Abstract. This study aims to determine the planning process, implementation and results of the application of the Dictation å¬å†™ (TÄ«ngxiÄ›) method in improving the vocabulary of Mandarin for grade VII students of SMP Kalam Kudus Makassar. Data collection methods used were tests, observation and documentation. This research consists of two types, namely qualitative and quantitative. This study consisted of two cycles and each cycle there were two meetings. The results showed that the average score obtained by students in the first cycle reached 75.28% and the second cycle reached 90.42%. These results indicate that the vocabulary of the seventh grade students of SMP Kalam Kudus Makassar increased by using the Dictation Method å¬å†™ (TÄ«ngxiÄ›).